A socio-psychological perspective on community participation in health during the Unidad Popular government: Santiago de Chile, from 1970 to 1973. (January 2014) - Hadjez-Berrios, Esteban
Community participation in health has conventionally been described and analysed from a non-historical perspective, neglecting the central role that disadvantaged communities have played in the construction of health institutions in our societies, alienating collective health from its historical subject. From a socio-psychological perspective, this study explores the experiences of community participation in health during the Unidad Popular government in Santiago de Chile from 1970 to 1973, evidencing a radical pedagogical process inside poor urban settlements, aimed to transform Chilean classist health institutions. These findings contribute to a critical understanding of community participation in health, conceived as a dialectic and transformative action.